Criticism of the Orientalist Approach in Islamic Studies: An Epistemological Analysis - Haswira Salleh Ahim (Penerbit Hellow Pustaka, 2026)
This study aims to examine the orientalist approach in Islamic studies which is often influenced by Western epistemological frameworks such as secularism, rationalism and empiricism, which leads to incommensurability in understanding Islamic teachings as a whole. Study problems arise if this approach tends to reduce revelation, question the authenticity of hadith and ignore Islamic scientific traditions, while at the same time producing interpretations that are not in line with the principles of Islamic aqidah and epistemology. To achieve the objectives of the study, a qualitative approach was used through library analysis of primary sources such as the Koran and hadith and sources including orientalist works and writings by Muslim scholars. The main objective of this study is to analyze the orientalist approach in Islamic studies and assess its epistemological weaknesses based on the Islamic epistemological framework which is based on revelation, reason and the scientific traditions of ulama. The results of the study show that the Orientalist approach contains several main weaknesses such as reductionism in revelation, skepticism towards hadith, use of Western hermeneutic methodology without adjustments. Apart from that, there is a significant epistemological incommensurability between Western and Islamic frameworks which causes the resulting interpretation to be non-holistic and less authentic. This study emphasizes that understanding Islam needs to be based on Islamic epistemology which integrates revelation, reason and ulama traditions to produce a more precise, balanced and authoritative analysis.